Writing Alone together: Richard E. Byrd's Antarctic classic and the challenges of reading collaborative autobiography. Issue 2 (2nd July 2016) - Schlick, Yaël
Abstract: Admiral Richard E. Byrd, known for his contested claim to have been the first person to fly over the North Pole and for his instrumental role in establishing the US presence in Antarctica, was also the author of the popular Antarctic adventure tale titled Alone . Published in 1938, the book was a media sensation. It relates Byrd's harrowing experiences while alone at a remote Antarctic meteorological station in the austral winter of 1934. But Byrd did not write Alone alone. Much of it was composed and edited by his ghostwriter, Charles Murphy. Using archival research, this essay explores the implications of Byrd's and Murphy's highly contentious collaboration for the interpretation of this work, and reveals the way Murphy's editorial command worked to highlight the work as a survival narrative in keeping with narratives of the Heroic Age of Antarctic exploration. The essay details and characterises the nature of Byrd and Murphy's disagreements over Alone, suggests how one might interpret this text in light of its plural authorship, and concludes with a discussion of the challenges of reading collaborative autobiographies more generally. I will refer occasionally to my initial reading and subsequent re-reading of this Antarctic classic in light of archival materials related to its composition as a means of gauging the way interpretation relies on assumptions and knowledge about the writing process.